Feministic blog articles and their influence on readers. - Chia, Wilson Wee Seng. (2013)
In this research, the effect and influence that feministic blog articles, otherwise known as bitchy blog articles, have on individuals and the various factors that will affect this influence are investigated. Grounding the arguments in various literatures on psychology and other disciplines, hypotheses were developed to show that the writing style of a blog article can influence the perspective of an individual differently. Proving the hypotheses developed, the results suggest that (1) a blog article with a feministic style of writing will have a higher degree of influence on an individual in changing their perception about an issue as compared to a blog article with similar content written in a neutral style. Ceteris paribus, (2) men are more susceptible to be influenced by the feministic blog article than women as women are more selective and discriminating against feministic blog articles despite being more familiar with them. Lastly, (3) individuals in positive moods are more likely to have their perceptions on an issue changed after being exposed to the feministic blog article compared to individuals in negative moods as individuals with negative moods tend to apply much more effort and are more analytical in their information processing.